Towards sustainable coastal development : institutionalizing integrated coastal zone management and coastal climate change adaptation in South Asia - Puthucherril, Tony George (Legal aspects of sustainable development, 2015)
Utilizing the coastal problems of South Asia, including sea level rise, Towards Sustainable Coastal Development: Institutionalizing Integrated Coastal Zone Management and Coastal Climate Change Adaptation in South Asia investigates the role of law and regional regimes in facilitating linkages between integrated coastal zone management and coastal climate change adaptation to contribute to sustainable coastal development.